PENGARUH PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN TERHADAP PERKEMBANGAN MOTORIK DAN KARAKTER PESERTA DIDIK SEKOLAH DASAR - Chandra Kurniawan; Ahmad Fardiansyah; Eka Yoga Adi Nur Putra; Wahyu Fitrah Al Zikri; Ely Yuliawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of Physical Education, Sports, and Health (PJOK) learning on the motor development and character building of elementary school students. The research method used is a literature review with a descriptive qualitative approach. Data sources were obtained from accredited national journals published between 2022 and 2025 that are relevant to the research topic. The results indicate that PJOK learning has a positive effect on improving students’ motor development, particularly gross motor skills, through structured and varied physical activities. In addition, PJOK learning also contributes to the development of students’ character, including discipline, cooperation, responsibility, and sportsmanship. Well-implemented PJOK learning supports holistic student development, both physically and morally. Therefore, PJOK should be continuously developed as an essential component of elementary school education.